Predictors of having heard about human papillomavirus vaccination: Critical aspects for cervical cancer prevention among Colombian women - Silvia Bermedo-Carrasco; Cindy Xin Feng; Juan Nicolás Peña-Sánchez; Rein Lepnurm (Elsevier, 2015)
Objectives: To determine whether the probability of having heard about human papillomavirus (HPV) vaccination differs by socio-demographic characteristics among Colombian women; and whether the effect of predictors of having heard about HPV vaccination varies by educational levels and rural/urban area of residence. Methods: Data of 53,521 women aged 13-49 years were drawn from the 2010 Colombian National Demographic and Health Survey. Women were asked about aspects of their health and their socio-demographic characteristics. A logistic regression model was used to identify factors associated with having heard about HPV vaccination. Educational level and rural/urban area of residence of the women were tested as modifier effects of predictors. Results: 26.8% of the women had heard about HPV vaccination. The odds of having heard about HPV vaccination were lower among women: in low wealth quintiles, without health insurance, with subsidized health insurance, and those who had children (p < 0.001). Although women in older age groups and with better education had higher probabilities of having heard about HPV vaccination, differences in these probabilities by age group were more evident among educated women compared to non-educated ones. Probability gaps between non-educated and highly educated women were wider in the Eastern region. Living in rural areas decreased the probability of having heard about HPV vaccination, although narrower rural/urban gaps were observed in the Atlantic and Amazon-Orinoquía regions. Conclusions: Almost three quarters of the Colombian women had not heard about HPV vaccination, with variations by socio-demographic characteristics. Women in disadvantaged groups were less likely to have heard about HPV vaccination.